Financial transaction taxes: Announcement effects, short-run effects, and long-run effects - Sebastian Eichfelder; Mona Lau; Felix Noth (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2017)
We analyze the impact of the French 2012 financial transaction tax (FTT) on trading volumes, stock prices, liquidity, and volatility. We extend the empirical research by identifying FTT announcement and short-run treatment effects, which can distort difference-in-differences estimates. In addition, we consider long-run volatility measures that better fit the French FTT's legislative design. While we find strong evidence of a positive FTT announcement effect on trading volumes, there is almost no statistically significant evidence of a long-run treatment effect. Thus, evidence of a strong reduction of trading volumes resulting from the French FTT might be driven by announcement effects and short-term treatment effects. We find evidence of an increase of intraday volatilities in the announcement period and a significant reduction of weekly and monthly volatilities in the treatment period. Our findings support theoretical considerations suggesting a stabilizing impact of FTTs on financial markets.
Additional information: A completely revised version of this paper has been published as Eichfelder, Sebastian; Noack, Mona; Noth, Felix: The Impact of Financial Transaction Taxes on Stock Markets: Short-run Effects, Long-run Effects, and Reallocation of Trading Activity. IWH Discussion Papers 12/2022. Halle (Saale) 2022. http://hdl.handle.net/10419/251589; More recent version: http://hdl.handle.net/10419/251589
Keywords: G02; G12; H24; M41; 330; financial transaction tax; market quality; announcement effect; short-run treatment effect